Work Life Balance ditinjau dari Stres Kerja pada Karyawan/karyawati - Jennifer Aoerora; Winida Marpaung (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
Conducted Research on employees at PT. Jaya Anugrah Sukses Abadi Medan to find out the relationship between work stress with work-life balance. All employees who work at PT. Jaya Anugrah Sukses Abadi Gatot Subroto Medan was made the subject of this research, totaling 120 people. The Sampling for this research based on the determination of a certain sample size with an error level of 5% with a population of 120 people, then used a sample of 89 people. The technique used for data analysis is the validity test, reliability test, normality test, linearity test. The test result on Pearson Product Moment Correlation prove that there is a strong and significant negaive relationship between work stress and Work-life balance with coefficient of -0.737 with p = 0.000 (p <0.05), and the value of R square (R²) = 0.543